Controlled release of donopezil-loaded polyvinyl alcohol (pva) microbubbles/nanoparticles using microfluidic t-junction device - CESUR, SÜMEYYE; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (My University, 2020)
Production of donepezil- loaded microbubble/nanoparticles for treatment of Alzheimer disease
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Microbubble; nanoparticle; microfluidic device; drug delivery; donepezil; alzheimer